Hydropower Landscape and Energy Diplomacy as Strategic Priorities of Nepal - Dhungel, Rudra Prasad (Journal of Interdisciplinary Studies, 2026)
Nepal’s hydropower development stands as one of the most influential energy transition cases in South Asia. Over the span of two decades, it has transformed from a state of chronic power shortages and reliance on electricity imports to, as of early 2025, a major actor with an installed power capacity of nearly 3,591 megawatts, well-positioned to emerge as a regional energy exporter. This paper conducts its analysis centered on the core analytical perspective of “energy statecraft”, a framework that refers to the proactive deployment of energy resources to advance diplomatic goals and reduce structural vulnerabilities. The study, based on a systematic analysis of Nepal’s 15th and 16th Periodic Plans, bilateral energy agreements and secondary literature on the nexus of energy economics and South Asian geopolitics, finds a substantial gap in the existing scholarship. While hydropower development in Nepal has been a subject of much technical and economic analysis, its instrumentalization as a foreign policy tool remains theoretically underdeveloped. This article addresses this gap by analyzing how energy export commitments, including 10,000 MW long-term supply agreements with India and 9,000 MW with Bangladesh, have been incorporated into Nepal’s diplomatic stance and regional positioning. The analysis reveals an eminent stress between Nepal’s statecraft ambitions and its structural limitations. Export reliability is constrained by seasonal generation asymmetries, limited cross-border transmission infrastructure, and asymmetric geopolitical dynamics of the India-Nepal-China triangle. Also, the intermittent governance vacuums and absence of stable energy policy frameworks undermine investor confidence and the sustainability of long-term projects. The study argues for a conceptual and functional shift in hydropower from a resource for domestic development to an active tool for projecting national power, but contends that this transformation is institutionally unsupported. Turning energy potential into credible statecraft requires more than megawatt capacity but demands a coherent governance architecture, transmission sovereignty, and policy continuity across electoral cycles.